2004
DOI: 10.1093/hmg/ddh271
|View full text |Cite
|
Sign up to set email alerts
|

Hypermutability in a Drosophila model for multiple endocrine neoplasia type 1

Abstract: Multiple endocrine neoplasia type I (MEN1) is an autosomal dominant cancer predisposition syndrome, the gene for which encodes a nuclear protein, menin. The biochemical function of this protein has not been completely elucidated, but several studies have shown a role in transcriptional modulation through recruitment of histone deacetylase. The mechanism by which MEN1 mutations cause tumorigenesis is unknown. The Drosophila homolog of MEN1, Mnn1, encodes a protein 50% identical to human menin. In order to furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 57 publications
6
51
0
Order By: Relevance
“…Recent progress in studying the function of menin suggests that menin has diverse functions, including regulation of gene transcription (Agarwal et al, 1999;Kaji et al, 2001;Lin and Elledge, 2003;Hughes et al, 2004;La et al, 2004a;Schnepp et al, 2004b), cell proliferation (Kim et al, 1999;Kaji et al, 2001;La et al, 2004b;Ratineau et al, 2004;Schnepp et al, 2004a), apoptosis (Sayo et al, 2002;Schnepp et al, 2004b) and genome stability (Scappaticci et al, 1992;Jin et al, 2003;Busygina et al, 2004). Menin is primarily a nuclear protein and possesses two classic nuclear localization signals, NLS1 and NLS2 (Guru et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in studying the function of menin suggests that menin has diverse functions, including regulation of gene transcription (Agarwal et al, 1999;Kaji et al, 2001;Lin and Elledge, 2003;Hughes et al, 2004;La et al, 2004a;Schnepp et al, 2004b), cell proliferation (Kim et al, 1999;Kaji et al, 2001;La et al, 2004b;Ratineau et al, 2004;Schnepp et al, 2004a), apoptosis (Sayo et al, 2002;Schnepp et al, 2004b) and genome stability (Scappaticci et al, 1992;Jin et al, 2003;Busygina et al, 2004). Menin is primarily a nuclear protein and possesses two classic nuclear localization signals, NLS1 and NLS2 (Guru et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary sequence of menin is highly conserved from fly to human, it does not bear obvious homology to known protein motifs, making it difficult to elucidate its biochemical function. Recent progress showed that menin regulates cell proliferation (5-7), apoptosis (8,9), and genome stability (10)(11)(12). Many of these functions rely on the ability of menin to regulate transcription of various genes, including cyclin-dependent kinase inhibitors and caspase 8 (9,13).…”
mentioning
confidence: 99%
“…9 -13 However, several investigations suggest that MEN1 may be involved in the maintenance of genomic integrity in a manner similar to that of BRCA1 and BRCA2 or the genes underlying HNPCC, which also show LOH in tumors. 14,15 The discovery of the MEN1 gene by positional cloning in 1997 resulted in the development of genetic tests for responsible mutations. 16,17 Dispersed nonsense, missense, frameshift, in-frame deletions, and splice-site mutations have been described in the syndrome, with the majority of pedigrees having unique mutations.…”
mentioning
confidence: 99%